Roles of cerebrospinal fluid-contacting neurons as potential neural stem cells in the repair and regeneration of spinal cord injuries - Xiong, Yanxiang; Pi, Wenjun; Zhao, Wang; Shi, Weiwei; Yan, Weihong; Yang, Hao; Zhou, Yuanrong; Li, Qing; Yang, Leiluo (Frontiers in Cell and Developmental Biology, 2024)
Cerebrospinal fluid-contacting neurons (CSF-cNs) represent a distinct group of interneurons characterized by their prominent apical globular protrusions penetrating the spinal cord's central canal and their basal axons extending towards adjacent cells. Identified nearly a century back, the specific roles and attributes of CSF-cNs have just started to emerge due to the historical lack of definitive markers. Recent findings have confirmed that CSF-cNs expressing PKD2L1 possess attributes of neural stem cells, suggesting a critical function in the regeneration processes following spinal cord injuries. This review aims to elucidate the molecular markers of CSF-cNs as potential neural stem cells during spinal cord development and assess their roles post-spinal cord injury, with an emphasis on their potential therapeutic implications for spinal cord repair.